Elemental composition of dust aerosols near cement plants based on the study of samples of the solid phase of the snow cover; Pure and Applied Chemistry; Vol. 94, iss. 3 - Volodina D. A. Daria Anatoljevna; Talovskaya A. V. Anna Valerievna; Devyatova A. Yu. Anna Yurievna; Edelev A. V. Aleksey Viktorovich; Yazikov Y. G. Yegor (Egor) Grigoryevich (2022, 2022)
Title screen